Evaluasi Penerapan Aplikasi Sistem Keuangan Desa (Siskeudes ver. 2.0.3) dalam Peningkatan Kinerja Aparat Desa menggunakan Task Technology Fit - Wawan Laksito Yuly Saptomo; Iwan Prasetyo; Bambang Satrio Nugroho; Elistya Rimawati (STMIK Sinar Nusantara, 2022)
The Village Financial System (Siskeudes) is an information system that assists the village government in reporting transparent and accountable financial reports. On the other hand, there are adjustments to financial management during the Covid-19 pandemic, so Siskeudes application also needs to accommodate these adjustments. Moreover, various problems were found in this system such as delays in financial reporting and recording errors. One of the factors of the problem is the mismatch of tasks in operating the application. This study aims to analyze the causes and consequences of task mismatches using the Task Technology Fit (TTF) model. The study described in this paper used the technology-to-performance chain as a framework to address the question of how task–technology fit influences the performance impacts. Respondents in this study were 50 village officials in Boyolali district who had used Siskeudes Ver. 2.0.3. This study was analyzed using a questionnaire with closed questions and open questions. This research method used Partial Least Square (PLS) using SmartPls 3.3.3. In addition, the results of this study indicated that the task of the technology-fit model has a significant effect on Performance Impact. Villages also have apparatus in accordance with Siskeudes operations. In this case, the finance department (having knowledge in finance) have a better level of performance. However, there are some villages where the operation of Siskeudes assisted by non-financial officials so that utilization does not have a significant effect on improving the performance of the finance department.